Biomass char gasification for hydrogen production: A thermodynamic equilibrium analysis - Shaolin Liu; Amine Ben-Abdelwahed; Cécile Gaborieau; Jean Lachaud (Fuel Processing Technology)
Hydrogen can be produced from biomass via thermochemical conversion, either through direct gasification of raw biomass or a two-step process involving pyrolysis to generate char, followed by char gasification. The latter process reduces tar contamination in syngas and improves gasification efficiency. Chemical equilibrium modeling of char gasification provides valuable estimates of ideal operating conditions, serving as an effective tool for gasifier design and optimization. The analysis focuses on the effects of process parameters on hydrogen yield and efficiency, as well as the determination of optimal thermodynamic conditions for hydrogen production. The chemical composition of wood char at different pyrolysis temperatures was examined using literature data. Char gasification in steam was predicted using Gibbs energy minimization, identifying up to 122 product species. The optimal conditions were identified within a temperature range of 900–1300 °C and a steam-to-char molar ratio (m) of 0.6–0.9, yielding a hydrogen molar fraction of 0.53 ± 0.01. Under these conditions, the primary gases produced were H2 (0.53) and CO (0.45). Further optimization of process efficiency suggested that setting the gasification temperature to 800 °C and the steam-to-char molar ratio to 1.3 could achieve a hydrogen molar fraction of 0.5 while maintaining a process efficiency of 55%.